In situ hybridization and polymerase chain reaction methods for the detection of Epstein-Barr virus RNA in breast cancer specimens - Arif Shah, Izham Naquiddin Shah; Hassan, Zuridah; Sukor, Rashidah; Othman, Azizon; Allaudin, Zeenathul Nazariah (Academic Journals, 2011)
The role of Epstein-Barr virus (EBV) as a cofactor in breast cancer is controversial and its association with breast cancer varies. In this study, EBV was detected by using in situhybridization technique (ISH) to detect Epstein-barr virus encoded RNA1 (EBER1) transcripts. Archival formalin-fixed paraffin embedded breast cancer tissue samples (n = 139) and normal breast tissue (n = 20) obtained from Hospital Tuanku Ja’afar were sectioned, stained and examined microscopically for nuclear staining and by DNA amplification of the same gene. By ISH, 83/139 (59.7%) and 12/20 (60%) were EBV positives in the breast cancer tissues and normal tissues, respectively. On the other hand, confirmation by polymerase chain reaction (PCR) found that additional six samples (89/139 or 64%) breast cancer tissues were positive for EBER1 gene. To further confirm the identity of these amplified products, two samples (UiTM-53 and UiTM-73) were sequenced, BLAST, analyzed phylogenetically and was found to be 100% similar to the EBV EBER1 gene sequences already deposited in the GenBank (accession numbers AB065135, FN545286, EF187853 and DQ883818). These preliminary findings suggest that there is a correlation between EBV and breast cancer but need further testing with more samples to confirm the role of EBV.